Genotoxic and Antitumor Activity of Pollen Grains against Prostate Cancer Cell Line: Pharmaceutical Science-Botany for Medicinal science - Magdah Ganash (International Journal of Life Science and Pharma Research, 2022)
Since the use of engineered antioxidants and antitumor is under investigation, inferable from its likely poisonousness, scientists have deflected their thoughtfulness regarding the quest for characteristic sources to meet the human medication and diet requests. Therefore the study aimed to evaluate the antitumor and antioxidant activities of maize pollen grains against the Prostate Cancer Cell (Pc3) line. Maize pollen grains were collected by Bee through a pollen trap, and then subjected for flavonoids and alkaloids analysis by HPLC method. an in vitro assays, were used to test the antitumor properties, against Pc3 cells. Furthermore, its antioxidant potential was also evaluated by DPPH. The detected flavonoids were identified to be quercetin, luteolin kaempferol, rutin, apigenin and naringin and the alkaloids were quinolone, hydroxyindolenine and conofoline. The antitumor efficacy of pollen grains extract increased with concentration and reached to 94.92 % that similar to the toxicity % of adriamycin at 1000 µg/mL, however, the IC50 (339.81 µg) of pollen grains extract was highest than IC50 (58.07 µg) of adriamycin. At 500 µg/mL of pollen grains extract, morphological changes of Pc3 were recorded. These changes deformed more at 1000 µg/mL. DPPH scavenging activity was found to be 92.26 % at 1280 µg/mL of pollen grains extracted with IC50 425.4 µg/mL compared with IC50 (13.9 µg/mL) of the ascorbic acid. DNA fragmentation and quantitative RT-PCR examinations of Bax and Bcl-2 genes demonstrated that pollen grains extract induced cellular apoptosis of Pc3 cells. This study concluded that the maize pollen grains may applied as natural safe source for inhibit Pc3 Cells proliferation as well as applied as antioxidant.